Evaluation of a Commercially Available Organic Acid Product During Feed Withdrawal and its Relation to Carcass Shrink in Commercial Turkeys - Pixley, C.; Barton, J.; Vicente, J.L.; Wolfenden, A.D.; Hargis, B.M.; Tellez, G. (International Journal of Poultry Science, 2010)
The transport of live animals has important economic and welfare implications. A commercially-available organic acid product (Optimizer™) was added to the drinking water of commercial hen turkeys during preslaughter Feed Withdrawal (FW) in two trials. In trial 1, a total of 60 trailers from treated (OA) or control non-treated turkey houses were evaluated. Turkey farmers initiated water treatment on the day before pick up (8-12 h treatment according to label directions). Investigators recorded trailer numbers as they were loaded out of each house to confirm which trailers contained treated birds vs. control non-treated birds. Individual trailer weights were recorded upon arrival to the processing plant and again immediately prior to live hang. A significant reduction in rate of weight loss during holding at the processing plant was observed in the treated turkeys (719 g/min per OA treated trailer vs. 845 g/min per control trailer). In trial 2, two commercial market age turkey houses were selected and in each house, 400 birds were weighed and recorded as a representative sampling. The treated house received OA administered according to manufacturer’s directions continuously for 19 h. At the end of this time, 400 birds were weighed and recorded as a representative sampling. A significant (p<0.05) improvement of average body weights was observed in treated turkeys during 19 h (125 g treated vs. 35 g control), an average of 90 grams difference. Experiments are ongoing to measure water consumption during the FW that may explain the reduction in carcass shrinkage during transportation to the processing plant and increased body weights at the farm by increasing hydration of turkeys treated with OA.